PENGARUH PENDEKATAN PEMBELAJARAN DAN BELIEF TENTANG IPA TERHADAP KEMAMPUAN PENALARAN IPA - Nurul Q. Ahmad (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2015)
This study explores the influence of learning approach and belief in the ability of reasoning of natural sciences subject at the secondary schools in Tanjung Priok, North Jakarta. This study uses experimental method to design treatment by level 2 x 2. The population of the study is all students of secondary schools in Tanjung Priok subdistrict, Jakarta during study years of 2012-2013. The sample of the study is all students of SMPN 140 Jakarta. Sampling was selected using Multi Stage Random Sampling in order to obtain a sample of 40 students. Research hypotheses were tested using the analysis of variance (ANOVA). The study found that; (1) reasoning ability in the group of students who were given the approach of Visual, Auditory, and Kinesthetic (VAK) is higher than the reasoning ability groups of students were given the conventional approach in the subject of natural sciences, (2) there is an interaction effect between learning approach and belief in the ability of reasoning, (3) the ability of reasoning group of students who were given a higher VAK approach of a group of students who were given conventional approach to groups of students who have a high belief, and (4) the ability of reasoning groups of students were given lower VAK approach of a group of students who given the conventional approach to groups of students who have a low belief. The finding of this study would be beneficial for science teachers and for teachers of other subjects in general to implement VAK approach in enhancing and improving the reasoning ability of student in the subject of natural science.